Epidemics of the central nervous system infections caused by West Nile virus in the territory of the South Bačka District, Vojvodina, Serbia - Sević, Siniša Đ; Stefan-Mikić, Sandra; Šipovac, Dragana; Turkulov, Vesna; Milošević, Vesna; Hrnjaković-Cvjetković, Ivana (Vojnosanitetski pregled, 2016)
Background/Aim. West Nile virus (WNV) is a neurotropic RNA virus particle which belongs to the Flaviviridae family, genus Flavivirus. It is sustained in arthropods within the transmission cycle between the mosquitoes and birds. Most commonly (80% of cases) WNV infections are asymptomatic among people. Less than 1% of patients develop neuroinvasive forms of the disease – meningitis, encephalitis, or acute flaccid paralysis. The aim of the research was to determine most common clinical and laboratory manifestations, to emphazise the presence of comorbidities and outcomes of treatment among patients with WNV infection. Methods. This retrospective study, which was conducted in the period from January 1, 2012 to December 31, 2013, evaluated 32 patients who were diagnosed with WNV infection based on clinical findings, laboratory, and serological tests. To assess statistical significance we used χ2, and t-test. Results. The study involved 22 (69%) males and 10 (31%) females aged from 31 to 65 years. On admission, there were 16 (50%) febrile individuals, 27 (84.4%) with positive meningeal signs, 17 (53.2%) with pathological neurological signs, and 10 (31.3%) with consciousness disorders. WNV infection was confirmed by the method enzyme linked immuno sorbent assay (ELISA) in all the patients, while Reverse Transcription Polymerase Chain Reaction (RT-PCR) test was positive in 3 (30%) of the tested patients. Cardiovascular comorbidities dominated in 7 (21.9%) of the cases. Full recovery was accomplished in 87.5 % of the cases. Conclusion. The results of our study show that the absence of meningeal signs and fever on the day 7 of hospital treatment are indicators of good course and prognosis of neuroinvasive forms of WNV infection. Comorbidities do not increase the risk of disease. ELISA test is a sovereign diagnostic method. In most cases, after the administered symptomatic therapy, the complete recovery of patients was achieved. Key words: west nile virus; central nervous system viral diseases; diagnosis; treatment outcome; prognosis; serbia.